Comprehensive Assessment of Explosion Risk of Glass Shower Enclosures Based on Dempster-Shafer (D-S) Evidence Theory. (July 2020) - Li, Ying; Han, Lei; Lu, Xiaowei; Ning, Xiuli; Xu, Yingcheng
Abstract: In recent years, an increasing number of consumers have bought glass shower enclosures for their homes as their living standards continue to rise. However, despite the convenience the product has to offer, incidents of exploding glass shower enclosures have been arousing wider concerns among the public. This paper is intended to conduct a comprehensive assessment on the explosion risk of glass shower enclosure products based on the Dempster-Shafer (D-S) evidence theory by establishing a glass shower enclosure explosion risk system, so as to provide a reference for reducing the safety risk of glass shower enclosure products.